Why Transnational Class and State? A Response to Ian Taylor. Issue 1 (February 2018) - Ougaard, Morten
Ian Taylor challenges the concepts of a transnational capitalist class (TCC) and state, suggesting that Poulantzas's notion of the "internal bourgeoisie" is a better theoretical starting point for the analysis of transnational class formation and that the transnational state (TNS) is a step too far. This critique is not convincing. It is debatable to what extent it is a "Poulantzian reading." The rejection of the notion of a TCC is unsustainable because of compelling evidence for the existence of such a class with articulated shared interests and organizations tasked with pursuing them. The critique of the TNS has some validity, but largely because proponents of the concept have been insufficiently clear on the consequences of upscaling the state concept to the global level. When this is acknowledged, the relevance and usefulness of the concept is that it enables state theoretical analysis of demonstrably existing TNS apparatuses that perform TNS functions, shaped by transnational relations of power between social forces, involving both structural power and direct engagement in transnational sites of contestation. There are now transnational elements of all fundamental characteristics of the capitalist state except one, the monopoly on the legitimate use of violence. Finally, Taylor does not provide an alternative approach to theorizing what descriptively is known as global governance.